2021
DOI: 10.1002/onco.13857
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib Monotherapy for Refractory Metastatic Colorectal Cancer: A Double-Blinded, Placebo-Controlled, Randomized Phase III Trial (ALTER0703)

Abstract: Background. Treatment options for refractory metastatic colorectal cancer (mCRC) were limited. Anlotinib is a novel multitarget tyrosine kinase inhibitor. ALTER0703 study was conducted to assess efficacy and safety of anlotinib for refractory mCRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…In the present study, most of the adverse events in patients received anlotinib therapy were grade 1-2 in severity. The incidence of secondary hypertension, hand-foot syndrome, and proteinuria was consistent with previous relevant clinical trials ( 36 ). Antiangiogenic drugs may increase the risk of bleeding.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, most of the adverse events in patients received anlotinib therapy were grade 1-2 in severity. The incidence of secondary hypertension, hand-foot syndrome, and proteinuria was consistent with previous relevant clinical trials ( 36 ). Antiangiogenic drugs may increase the risk of bleeding.…”
Section: Discussionsupporting
confidence: 88%
“…Grade 3-4 adverse reactions occurred in 15 (34.9%) patients. Anlotinib related AEs were consistent with the known safety profiles of anti-angiogenesis therapy, including secondary hypertension, hand-foot syndrome and proteinuria (27)(28)(29). Most AEs mainly come from chemotherapy and immunotherapy.…”
Section: Discussionsupporting
confidence: 68%
“…In lung cancer, third-line monotherapy (37) or second-line chemotherapy (38,39) combined with immunotherapy (40) has been effectively applied. Studies have achieved effective results not only in NSCLC and SCLC (10), but also in liver cancer (19,41) or refractory metastatic colorectal cancer (42). There are currently more (15) revealed that anlotinib had a profound inhibitory effect on ribosomes, and regulated the cell cycle, RNA metabolism, and lysosomes as determined by transcriptomics, proteomics, and phosphor proteomics profiling.…”
Section: Discussionmentioning
confidence: 99%